Access to education for Ethiopian refugees in Cairo: a refugee centered approach - Wijtsma, Cynthia (AUC Knowledge Fountain, 2019)
This thesis looked at the access to education for Ethiopian refugees in Cairo. Due to legal constraints, Ethiopian refugees do not have access to the Egyptian public school system and are often unable to afford the private schools. Many Ethiopian refugees are therefore depending on non-formal forms of education. This study aimed to look at which forms of education Ethiopian refugees access, and how they access these forms. To do so, ethnographic research and interviews were conducted among several Ethiopian refugee communities and different stakeholders in the field of education. This study found that in contrast to general understanding, Ethiopian refugees often do not access the Sudanese community schools. Rather, they opt for either the so called ‘Nigerian Schools’ or the nurseries. The reason for this is two-fold. First, many shy away from the Sudanese due to their previous experience in Sudan or the stories and rumors they have heard of robbery and kidnapping in Cairo. Secondly, parents want to prepare their children as much as possible for the future and therefore opt for an English medium school. Education, therefore, was not just an isolated topic, but an aspect deeply connected to past life experiences, present life and future life. Education is not something that refugees passively receive, but actively seek. Therefore, looking at the access to education through the lens the autonomy of migration can serve as a space where refugees assert autonomy and claim their citizenship rights. Through taking a refugee centered approach, the topic of access to education changes from one that describes the educational opportunities provided for Ethiopian refugees, to one that describes ways through which Ethiopian refugees have found their way in the patchwork of educational opportunities and have asserted their autonomy.